Planthopper-rice interactions: unequal stresses on pure-line and hybrid rice under similar experimental conditions - Crisol, Eduardo; Almazan, MLP; Jones, P.W.; Horgan, FG (Wiley, 2013)
Hybrid and pure‐line (inbred) rice [Oryza sativa L. (Poaceae)] varieties have distinct physiologies, particularly as related to their nutrient requirements. These differences could confound the results and interpretation of experiments that compare rice varieties grown in pots for their resistance and responses to herbivores. In this study, a series of experiments was conducted to identify potentially confounding interactions between pot size (soil volume), fertilizer regime, and the use of acetate insect cages with rice line type (hybrid, fertile parental inbred, and male sterile inbred) during bioassays with the brown planthopper, Nilaparvata lugens (Stål) (Hemiptera: Delphacidae). The growth of hybrid rice was often limited (relatively low biomass and low grain production) compared to fertile inbred lines even in large pots (7 200 ml) and when grown without added fertilizer. Several interactions between the effects of growth conditions and line type were detected. Acetate cages caused a significant reduction in grain yield in hybrids, but not in inbreds, mainly resulting from a cage‐induced decrease in grain weight (smaller grains). Hybrids and male sterile lines often had higher root or above‐ground biomass in the largest caged pots compared with fertile inbred lines, but biomass was similar in smaller pots, indicating that the large pots allowed longer unimpeded growth of fertile inbreds, but not other line types. There were no interactions between the presence or absence of planthoppers with line type or experimental conditions. All line types were equally susceptible to planthoppers. Often the effects of planthopper feeding on plant fitness (i.e., tolerance) were apparent when plants were grown in large pots but not in small pots, particularly for hybrid lines and under high nitrogen regimes. On the basis of these results we recommend that researchers ensure that plants are not unequally stressed by inadequate growth conditions during comparative studies with herbivores on physiologically distinct rice varieties or rice species. We recommend the use of large pots (soil volume) and lower fertilizer levels with young, non‐reproductive plants during comparative bioassays with planthoppers. Field cages are recommended for hybrid‐inbred comparisons during older plant stages but these are subject to a range of other confounding variables.